Gray matter differences between affective and non-affective first episode psychosis: A review of Magnetic Resonance Imaging studies - Calvo, Ana; Delvecchio, G; Altamura, A C; Soares, J C; Brambilla, P (Journal of Affective Disorders, 2018)
Background Non-affective and affective psychoses are very common mental disorders. However, their neurobiological underpinnings are still poorly understood. Therefore, the goal of the present review was to evaluate structural Magnetic Resonance Imaging (MRI) studies exploring brain deficits in both non-affective (NA-FEP) and affective first episode psychosis (A-FEP). Methods A bibliographic search on PUBMED of all MRI studies exploring gray matter (GM) differences between NA-FEP and A-FEP was conducted. Results Overall, the results from the available evidence showed that the two diagnostic groups share common GM alterations in fronto-temporal regions and anterior cingulate cortex. In contrast, unique GM deficits have also been observed, with reductions in amygdala for A-FEP and in hippocampus and insula for NA-FEP. Limitations Few small MRI studies with heterogeneous methodology. Conclusions Although the evidences are far to be conclusive, they suggest the presence of common and distinct pattern of GM alterations in NA-FEP and A-FEP. Future larger longitudinal studies are needed to further characterize specific neural biomarkers in homogenous NA-FEP and A-FEP samples.
Keywords: magnetic resonance imaging; gray matter; first episode psychosis; affective; non-affective; Scopus; JCR